Marriage and family: the quest for intimacy - Lauer, Robert (Boston: McGraw Hill, 2000)
Contents: The context of intimacy. Seeking intimate relationships. The intimate couple. Intimacy in families. Challenges to intimacy
Includes bibliographical references and index
Keywords: Familia - Matrimonio